THE INVERSE-SCATTERING PROBLEM SOLUTION AND SHAPE FROM THE REFLECTED ELECTROMAGNETIC WAVE FIELD STRUCTURE - A. I. Kozlov; V. Yu. Maslov (Научный вестник МГТУ ГА)
The reflected field calculation from the object can be described with the set of point reflectors with the coordinates in electromagnetic wave plane of incidence corresponding to two-dimensional grid nodes with rather small-sized step. At the same time, the single scattering model which does not consider the re-reflection and point elements cross impact is used in the reflected field calculations. The rapid direct and inverse transformation algorithm is used. The numerical solution algorithms of the direct and inverse scattering problems on the object are offered. The method uses the ray representations scattering fields which are based on the Huygens-Fresnel principle. The graphic diagram of the reciprocal object positioning and the observation plane from the reflected electromagnetic field object is represented. The double reflecting Gaussian surface is graphically figured. The figures of the module and the complex amplitude electric field strength of the reflected wave from a double Gaussian surface argument are provided. To shape the surface of the unknown object the recovery shape algorithm is used, by means of reflected wave phase. This algorithm is based on finding the complex matrix elements in dependence on absolute phase, which is proportional to the appropriate point object distance.